Meet-in-the-middle meets multi-omics identifying molecular signatures of environmental drivers of childhood overweight - Congrong Wang; Brigitte Reimann; Tim S Nawrot; Dries S Martens; John Wright; Rosemary McEachan; Johanna Lepeule; Wenlun Yuan; Leda Chatzi; Marina Vafeiadi; Regina Grazuleviciene; Sandra Andrusaityte; et al. (Environment International)
Background: Obesity is a multi-cause chronic disease recognized across the lifespan, with childhood obesity prevalence rising over the past decades. Although exposome-wide association studies have identified early-life environmental drivers of child obesity, and explored the multi-omics signatures of the exposome of children, it is understudied whether the combined effects of multiple exposures are potentially mediated by multi-omics. Methods: Within the Human Early Life Exposome (HELIX) project, 1041 mother–child pairs were surveyed for a wide range of environmental exposures including over 354 prenatal and childhood exposures. Multi-omics molecular features were measured during childhood, encompassing the blood methylome and transcriptome, plasma proteins and urinary and serum metabolites. Exposome and multi-omics features were integrated into latent factors by Multi-omics Factor Analysis, based on which structural equation modelling was used to assess whether multi-omics mediated associations between exposome and child body mass index (BMI). Results: Key findings included: (i) prenatal nutrition, exercise, and passive smoking influencing BMI via DNA methylation of HOXA5 and Tenascin XB; (ii) childhood exposure to PCBs and phenols linked with BMI through inflammation and coagulation pathways; and (iii) childhood PCB and dietary exposures associated with BMI via immune pathways. Conclusions: This novel untargeted workflow elucidated biological mechanisms linking environmental exposures to child obesity, potentially supporting targeted public health interventions.